Methotrexate Has No Antifibrotic Effect in Bleomycin-induced Experimental Scleroderma - Ozgen, Metin; Koca, Suleyman S.; Isik, Ahmet; Ozercan, Ibrahim H. (J Rheumatol Publ Co, 2010)
[Abstract Not Available]
Keywords: Model; Fibroblasts; Placebo; Trial